Implementing self-monitoring to reduce inappropriate vocalizations of an adult with autism in the workplace. (February 2019) - Wills, Howard P.; Mason, Rose; Huffman, Jonathan M.; Heitzman-Powell, Linda
Highlights: The self-monitoring application resulted in a decline in inappropriate vocalizations. Overall, work engagement and hair pulling were not adversely affected by self-monitoring. Social validity suggested the application was easy to utilize. Abstract: Individuals with autism spectrum disorder (ASD) are capable of competitive employment and can work successfully in community businesses. However, it is common for individuals with ASD to be unemployed or underemployed at higher rates than other groups with disabilities and the population at large. ASD encompasses a range of behaviors with the potential to interfere with productivity within the workplace. Research has supported management of these behaviors, through methods such as self-monitoring, may improve community access and employment. A singlesubject withdrawal design was utilized to evaluate the functional relationship between implementation of the I-Connect self-monitoring intervention and inappropriate vocalizations, with secondary measurement of work engagement and hair pulling behaviors. An adult female with ASD received training on the use of the I-Connect self-monitoring application in her work place medical records setting. Introduction of the I-Connect self-monitoring application resulted in an immediate decrease in inappropriate vocalizations. Social validity measures suggest the application was easy to utilize and may be beneficial in increasing a person's perceived ability to regulate inappropriate vocalizations in a work environment.